2006
DOI: 10.1021/cm0605522
|View full text |Cite
|
Sign up to set email alerts
|

Partially Fluorinated, Polyhedral Oligomeric Silsesquioxane-Functionalized (Meth)Acrylate Resists for 193 nm Bilayer Lithography

Abstract: The influence of partial fluorination on the lithographic performance of photoresists based on (meth)acrylate terpolymers containing polyhedral oligomeric silsesquioxane (POSS) pendant groups is investigated in bilayer schemes for 193 nm lithography. For the first time the capability of POSS-functionalized resists for standard lithographic processing, including use of standard developer (0.26 N tetramethylammonium hydroxide) and industrial processing equipment is demonstrated. The optimized resists formulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The first component is the ethyl-substituted POSS methacrylic constituent (MAEPOSS). The influence of POSS substituents on the lithographic characteristics of the resist has been reported previously [25,26]. In addition, it has been shown that silsesquioxane cage groups demonstrate reduced k values because of the decreased material's density, which derives from the way that Si and O atoms are arranged in the silsesquioxane elementary unit [17,27].…”
Section: Composition Of Terpolymersmentioning
confidence: 89%
See 3 more Smart Citations
“…The first component is the ethyl-substituted POSS methacrylic constituent (MAEPOSS). The influence of POSS substituents on the lithographic characteristics of the resist has been reported previously [25,26]. In addition, it has been shown that silsesquioxane cage groups demonstrate reduced k values because of the decreased material's density, which derives from the way that Si and O atoms are arranged in the silsesquioxane elementary unit [17,27].…”
Section: Composition Of Terpolymersmentioning
confidence: 89%
“…Details on their synthesis are given elsewere [25]. The photoacid generator (PAG), triphenylsulfonium perfluorooctylsulfonate (TPS-PFOS) was obtained from Midori Kagaku.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the fact that caged type POSSs have internal space and good property of dielectric constants, they have been incorporated into polymer matrices to obtain low dielectric constant materials [14][15][16][17][18][19][20]. In the optoelectronic applications, POSSs have been employed to improve the thermal stability of photo resist [21][22][23][24] and light emitting diode (LED), the response speed of electrochromic materials [25][26][27], and luminescence efficiency.…”
Section: Introductionmentioning
confidence: 99%